Are independent fact checkers effective in combatting fake news on COVID-19? A case study of Indonesia - Ridhanty, Anantia (2021)
Accessing the latest information is easier these days since the development and expansion of the new media. Unlike newspapers, radio, or television, the internet could give us the latest update about almost everything that happens worldwide quickly. One of the big events that have happened in 2020 is SARS-CoV-2, a virus that causes COVID-19 globally from the end of 2019. This virus has caused numerous deaths and scares most people since this kind of virus has never been discovered before. Therefore, this condition leads people to find any information as much as they can. However, some information on the internet is fake and misleading. To avoid consuming and spreading fake news in Indonesia, a group of people called “The fact-checkers” is debunking the fake news that spreads on the internet every day. This study conducts research on how “The fact-checkers” work and how influential they are to the government of Indonesia.